(untitled) (Journal of EAHIL, 2019)
The Medical Faculty and the University Medical Library of the University of Basel jointly developed a new learning unit called Searchaton. This learning unit aimed at providing knowledge for the point-of-care literature search in everyday clinical practice. To make this as practical and customer-oriented as possible, the faculty and library interacted closely with medical experts. During the Searchaton, the task was to translate a patient case into a clinical question and to find an answer to that question. The format combined collaborative working and gamification with an aspect of time pressure to better reflect everyday clinical situations. The participants benefited greatly from the intensive support and were able to assess their searching skills in the context of evidence-based clinical decision-making.